Geç tanı konmuş nazal yabancı cisim - (:unkn) unknown (My University, 2005)
Bu yazıda 30 yılı aşkın süredir tek taraflı burun tıkanıklığı ve kötü kokulu burun akıntısıyla seyreden, birçok kez şiddetli baş ağrısı nedeniyle akut sinüzit tedavisi uygulanan rinolit vakası tartışılmıştır. Tek taraflı burun tıkanıklığı ve pis kokulu burun akıntısı şikayetleriyle başvuran hastalar yabancı cisim düşünülerek hekimler tarafından ayrıntılı olarak değerlendirilmeli, hastalığın yaygınlığı ve hastanın uyumuna göre genel veya lokal anestezi altında nazofarinkse kaçırmadan çıkartılmalıdır.

In this article we discussed a patient with rhinolithiasis who has been complaining of unilateral nasal blockage and foul smelling rhinorhea for over 30 years. In this period this patient was treated several times with diagnosis of sinusitis. Patients who presents with a long standing nasal obstruction and foul smelling rhinorhea must be well evaluated by physicians, keeping in mind the possibility of nasal foreign bodies. Depending on the patients degree of cooperation the foreign body should be extracted carefully under local or general anesthesia taking care not to dislodge it in to the nasopharynx.
Late diagnosed nasal foreign body
Keywords: Tıbbi Araştırmalar Deneysel; Kulak, Burun, Boğaz